Pengaruh Air Kelapa Terhadap Pemulihan Kerja Kardiovaskular Setelah Latihan Aerobik Submaksimal - Risma Abbas (Jurnal Ilmiah Tarbiyah Umat, 2019)
Many changes occur in the body during exercise to meet growing energy needs, one of which increase cardiovascular work. Rapid reduction in cardiovascular critical work in supporting physical abilities to the next activity. One aspect of recovery is to restore body fluids and electrolytes lost with sweat during exercise where one effect is to lower the cardiovascular work after exercise. Coconut water contains minerals and electrolytes resembles a human body fluids so easily exploited and have the highest body potassium which serves for the regulation of the heart. This study examines the effect of coconut water in the recovery of cardiovascular work by measuring the amount of decrease in blood pressure and pulse rate after submaximal aerobic exercise with Ergocycle at 80% HRmax limit. The subjects used were Nikken UNESA badminton athlete as many as 18 subjects acted as a control and treatment. Observations between pemeberian mineral water and coconut water as a control treatment within cypress week. Measurement of the amount of blood pressure and pulse rate before and immediately after exercise and repeated 10 times with each measurement interval of one minute 20 seconds after administration of mineral water and coconut water. The data were the mean measurements of one to 10 to see the decline after treatment indicates the amount of water given blood pressure between the control and treatment differ significantly p < 0.005, pulse frequency was also significantly different p < 0.005. Rapid decline observed in the observation delta pulse and blood pressure control immediately after exercise treatment and observation to 10 with results significantly different p < 0.005. The results showed a faster recovery of cardiovascular work by giving coconut water than mineral water with seeing a decrease in pulse rate and blood pressure after submaximal aerobic exercise.